Design Of Application Proposal Formation Government Internal Auditor Functional Position - Muhammad Ari Ardiansyah; Zulhalim Zulhalim; Rumadi Hartawan; Ito Riris Immasari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Functional Auditor Development Center (Pusbin JFA) as a supervisor of government internal functional audit has a constraint to publish recommendation formation of auditor for Government Internal Oversight Apparatus (APIP). The current process is still running manually and slowly, so that need the application which makes APIP unit easier to compile proposals and speed up the verification and validation process at Pusbin JFA then the auditor's recommendation publishing process getting better. Laravel framework was matched to handle this application, which is website based. This framework was easy to use and accelerate the process for develop program or application, and then it was combined with Extreme Programming (XP) development method system where this method was matched to use in government institution or the place where the developer was limited. As long as use this Laravel framework and XP method, all of the application development process has been streamlined so this application can be implemented soon.